Delivery of Native Proteins into C. elegans Using a Transduction Protocol Based on Lipid Vesicles. Issue 1 (December 2017) - Perni, Michele; Aprile, Francesco; Casford, Sam; Mannini, Benedetta; Sormanni, Pietro; Dobson, Christopher; Vendruscolo, Michele
Abstract The nematode wormCaenorhabditis elegans (C. elegans ) is a versatile and widely used animal model forin vivo studies of a broad range of human diseases, in particular for understanding their genetic origins and for screening drug candidates. Nevertheless, the challenges associated with the administration of native proteins toC. elegans have limited the range of applications of this animal model in protein-based drug discovery programs. Here, we describe a readily usable protocol for the transduction of native proteins inC. elegans, which is based on the encapsulation of the proteins of interest within cationic lipid vesicles, prior to their administration to worms. This procedure limits the degradation of the proteins in the guts of the animals, and promotes their adsorption into body tissues. To illustrate the efficacy of this approach we apply it to deliver an antibody designed to inhibit α-synuclein aggregation, and show that it can lead to the rescue of the disease phenotype in aC. elegans model of Parkinson's disease. As this transduction protocol is fast and inexpensive, we anticipate that it will be readily applicable to protein-based drug discovery studies that utilizeC. elegans as a model organism.